Private sanctions - Oliver D. Hart; David Thesmar; Luigi Zingales (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2022)
We survey a representative sample of the U.S. population to understand stakeholders' desire to see their firms exit Russia after the invasion of Ukraine. 61% of respondents think that firms should exit Russia, regardless of the consequences. Only 37% think that leaving Russia is a purely business decision. If a firm does not conform with these desires, 66% of the respondents are willing to boycott it. This desire diminishes with the costs they face in boycotting. At 500, 43% would want to boycott. Our model is able to explain up to 24% of the cross-sectional variability in attitudes to boycotting. Nevertheless, it is difficult to separate deontological and consequentialist motives to boycott, because subjects' beliefs are highly correlated with values. When we randomize the beliefs we find a strong effect for shareholders, but not for the other stakeholders. We discuss what are the geopolitical and economic implications of a world where private corporations discontinue profitable business relationships for moral or political reasons.
Keywords: 330